A linkage of monetary policy and conventional-Islamic stocks: Indonesia evidence - Nora Ria Retnasih (Center for Economics, Business and Entrepreneurship Development Faculty of Economics and Business, Universitas Muhammadiyah Malang, 2022)
This research aims to analyze the relationship between monetary economic variables (money supply, inflation, exchange rates, and BI rate) toward the index of sharia stock value (JII) and conventional stock index values (LQ45) over a short and long period. Moreover, predicting the value of each index in the future period is also another objective of this research. The methods used in this quantitative research are Vector Error Correction Model (VECM). The data analyzed in this research is monthly data from January 2019 to December 2021. The result of the long-term VECM test shows that inflation, exchange rate, and BI rate significantly affect both stock indexes. Meanwhile, the result of the short-term test, the money supply affects the JII index, and inflation affects both of the indexes. The results of the IRF test show that the response of LQ45 and JII is very small on monetary variable shocks with a stable value in the long term. The results of the FEVD test show that the variation in the LQ45 is affected by monetary variables in a small percentage, while the effect on the JII is quite high.